A Review of Coronavirus Disease (COVID-19) in Children - Ghodsi, Alireza; Azarfar, Anoush; Ghahremani, Sara (Journal of Pediatric Nephrology, 2020)
Abstract: Since December 2019, an outbreak of coronavirus disease 2019 (COVID-19) with a high morbidity and mortality rate has spread globally and affected all age groups. Children can carry and transmit the novel coronavirus, but usually do not develop severe disease. The number of children who contracted coronavirus disease 2019 has increased significantly; however, compared to adults, there have been fewer reported cases of COVID-19 in the pediatric population. This review is mainly about the epidemiological features, clinical findings, laboratory tests, imaging, and treatment recommendations in children with COVID-19 disease.